2015
DOI: 10.1016/j.solener.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Full scale experimentation on a new translucent passive solar wall combining silica aerogels and phase change materials

Abstract: International audienceThis paper presents the first passive solar wall providing simultaneously super insulation, heat storage and daylighting to the inner space. The wall’s external layer is composed of a silica aerogels bed for high insulation and solar radiation transmission. The second layer, internal, is composed of glass bricks filled with a eutectic phase change material (PCM) for heat storage and restitution. The whole wall is translucent. The experimentations carried out to characterize thermal and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 29 publications
0
24
0
3
Order By: Relevance
“…For example, an experimental study carried out on a novel translucent full scale passive solar MEPCM wall by Berthou et al (Berthou et al, 2015) revealed that it could be used to provide significant improvement of indoor temperatures in both cold and sunny climates. Silva et al (Silva et al, 2015) evaluated the thermal performance of a novel PCM window shutter in a room and obtained a reduction in the maximum and minimum peak temperatures by 6% and 11% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an experimental study carried out on a novel translucent full scale passive solar MEPCM wall by Berthou et al (Berthou et al, 2015) revealed that it could be used to provide significant improvement of indoor temperatures in both cold and sunny climates. Silva et al (Silva et al, 2015) evaluated the thermal performance of a novel PCM window shutter in a room and obtained a reduction in the maximum and minimum peak temperatures by 6% and 11% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, silica has been extensively investigated in the fields of PCMs and heat storage. Berthou [23] has formed a new translucent passive solar wall by combining silica aerogels and PCMs; Min [2] has investigated PEG/mesoporous-silica-shape-stabilized PCMs; Chen [24] has utilized hydrophobic fumed silica for preparing form-stable composite PCMs; Qian [5] and He [25] have prepared shape-stabilized PEG/SiO 2 composites by sol-gel methods.…”
Section: Introductionmentioning
confidence: 99%
“…• the geographical distribution of the studies, which also provides an indication of the climatic conditions of the study; • the climatic/seasonal distribution of the studies: winter season (37%) [12][13][14][15][16][17][18][19][20][21][22], mid-season (10%) [14,15,20] and summer (50%) [13][14][15][16][17]20,[23][24][25][26][27][28][29][30][31] season periods; • the most investigated PCM typologies, that have been found to be paraffin wax (60%) [14][15][16]18,19,22,23,[25][26][27][28][29][30][31][32][33][34][35] and salt hydrates (20%) [12,13,…”
Section: Literature Review At a Glancementioning
confidence: 99%
“…• in all the papers, the PCM had been macro-encapsulated in containers, that is, glass containers (70%) [12][13][14][15][20][21][22][23][24][25]27,[30][31][32][33][34][35][38][39][40][41], polycarbonate containers (20%) [16,17,19,28,36,42] and aluminium containers (10%) [18,26,29]; • the technologies had predominantly been characterised in outdoor test cells (57%) [14,15,17-22, 24-27,29,31,35] and through laboratory analysis (53%) [12,13,17,20,23,[32][33][34][35][36][37][38][39][40][41][42], while some other studies had been carried out by coupling a modelling activity with an experimental activity (37%) …”
Section: Literature Review At a Glancementioning
confidence: 99%
See 1 more Smart Citation